REASSESSING INSURERS' ACCESS TO GENETIC INFORMATION: GENETIC PRIVACY, IGNORANCE, AND INJUSTICE - Feiring, Eli (Bioethics, 2009)
Many countries have imposed strict regulations on the genetic information to which insurers have access. Commentators have warned against the emerging body of legislation for different reasons. This paper demonstrates that, when confronted with the argument that genetic information should be available to insurers for health insurance underwriting purposes, one should avoid appeals to rights of genetic privacy and genetic ignorance. The principle of equality of opportunity may nevertheless warrant restrictions. A choice-based account of this principle implies that it is unfair to hold people responsible for the consequences of the genetic lottery, since we have no choice in selecting our genotype or the expression of it. However appealing, this view does not take us all the way to an adequate justification of inaccessibility of genetic information. A contractarian account, suggesting that health is a condition of opportunity and that healthcare is an essential good, seems more promising. I conclude that if or when predictive medical tests (such as genetic tests) are developed with significant actuarial value, individuals have less reason to accept as fair institutions that limit access to healthcare on the grounds of risk status. Given the assumption that a division of risk pools in accordance with a rough estimate of people's level of (genetic) risk will occur, fairness and justice favour universal health insurance based on solidarity.